Pendampingan Dalam Mengenalkan Kosa Kata Bahasa Arab Terhadap Anak-anak di Desa Cempaka Mulia Barat Melalui Pojok Litrasi Islami Program Mahasiswa KKN. - Rendy Adrian; Emia Sentiya; Rosiana Latifah; Vina Rahmawati (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
This service aims to provide guidance in introducing Arabic vocabulary (mufrodat) to children in Cempaka Mulia Barat Village through the KKN Islamic Literacy Corner program. The method applied is descriptive qualitative. Activities began with observation, coordinating with the village and school, preparing facilities and infrastructure, conducting pretests, carrying out mentoring, and holding posttests. The mentoring was carried out using the reading, writing and memorization method for number vocabulary, and using the singing method for vocabulary related to places. The results showed that the children were very enthusiastic and motivated in learning Arabic vocabulary in preparation for continuing their education to a higher level.